Effect of processing parameters on equal-channel angular pressing of aluminum alloys: An overview. (2021) - Saxena, Kuldeep K.; Basanth Kumar, k.; Gupta, Akash
Abstract: Equal-channel angular pressing (ECAP) is one of the emerging Severe plastic deformation (SDP) technique that makes ultra-fine grains (UFG) microstructure to improve the properties of different materials and composites. The uniqueness of the ECAP technique is that it can refine the grain size without changing the cross-section. Many factors like processing temperature, number of ECAP passes, die channel angle and processing route affects the results obtained from ECAP technique. This review is mainly focused on the mechanical and microstructural properties of aluminium alloys generated after ECAP Process along with number of passes. It is observed as the number of passes increased the hardness and tensile strength of the alloy increase and ductility of the material is reduced. The maximum percentage of grain refining is obtained in the first two or three passes after that no significant changes were observed because the effect of temperature is more than the effect number of passes on the grain size.